Non-Skeletal Manifestations of Vitamin D Deficiency- A Review (Journal of Medicine, 2012)
Objective: There are lots of important non-skeletal systemic consequence of vitamin D deficiency which was often was underestimated. The purpose of this review is to discuss the non-skeletal systemic manifestations of vitamin D deficiency. Data Sources: We searched Medline, Pub med, Google Scholar & individual searches. DOI: http://dx.doi.org/10.3329/jom.v13i1.10053 JOM 2012; 13(1): 65-68